PENGARUH KOMPETENSI, KOMUNIKASI, DAN KEPEMIMPINAN TERHADAP LOYALITAS KARYAWAN PADA CV ANDALAS KOMPUTER SURAKARTA - Djumali, Ngatman, Istiatin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this study is to know how big the influence of competence, communication, and leadership on employee loyalty in CV Andalas Surakarta. This research includes the type of quantitative research that explains the relationship between the variables and test the hypothesis. The population in this study is all employees in CV Andalas Komputer in Surakarta which amounted to 50 people. The entire population is taken as a sample. Methods of data collection using questionnaire / questionnaire. Data analysis technique using classical assumption test and statistical analysis to test hypothesis with multiple linear regression analysis, t test, F test, and test of coefficient of determination. The results showed that: Based on the F test (simultaneous) showed that competence, communication, and leadership simultaneously have a significant effect on employee loyalty and t test result (partial) indicate that competence, communication and leadership have positive effect on employee loyalty CV Andalas Komputer Surakarta individually (partial)Keywords: employee loyalty, competence, communication, leadership